Evaluasi Peningkatan Practical Skills Siswa SMK Melalui Pelaksanaan Pelajaran Pekerjaan Dasar Teknik Mesin Berbasis Work-Based Learning - Sabbihisma Fattah Hardianto Putro (Universitas Negeri Malang, 2020)
Abstract: work-based learning is work-based learning that is being developed in various vocational high schools to improve the practical skills that are owned by learners. Increasing practical skills can be maximally able to make it easier for learners to compete for work when passing the study of PDTM. The purpose of this research is to evaluate the learning outcomes using the work-based learning method with the CIPP method. This study uses a quantitative descriptive approach, with the type of poll instruments and performed on the PDTM subjects in SMK Turen. The subjects were reached by a tpm class of 10. 180 students and conducted research into 60 learners as sample trials and 120 learners as research samples. The data analysis techniques use descriptive and grouped the percentages of likert scales. Improved practical skills evaluated using cipp methods namely context, input, process, and product. The results showed that the study of pdtm in smk turen, which uses work-based learning method, can improve the practical skills of students well even though there are still some indicators that have to be improved. The expectation is in order to improve the skills of practical skills to maximum students. Keyword: work based learning, practical skills